External shocks, food security, and development: Exploring scenarios for Central America - Díaz-Bonilla, Eugenio; Piñeiro, Valeria; Elverdin, Pablo (International Food Policy Research Institute, 2016)
We conduct an ex ante evaluation of the impacts of a potential global recession within the next years and the possible policy responses to support economic activity and improve social indicators in five Central American countries: Costa Rica, El Salvador, Guatemala, Honduras, and Nicaragua. We review the economic and social evolution of the past decades in those countries, and we consider a global scenario that includes further deceleration of world growth, lower commodity prices, and a decline in remittances and capital flows to those countries. We simulate those scenarios and related policy issues using recursive dynamic CGE models for the countries considered. The global shock is run under fixed exchange rates and flexible exchange rates (in the case of El Salvador, which has adopted the US dollar as the domestic currency, the simulation of a flexible exchange rate is just indicative). In all cases, a flexible exchange rate delivers better results in terms of GDP per capita, by softening the overall economic impact of the external shocks. Two possible interventions to deal with the recession are simulated: one focuses on policies to strengthen the safety net for the poor; the other applies a more general macroeconomic stimulus (a tax cut plus a modest increase in public investments, financed by un-conventional monetary policy) to try to cushion the shock. For all countries except El Salvador, these two simulations are run with a flexible exchange rate. In the first policy simulation GDP per capita in those countries does not change much, but the poor groups targeted clearly improve their incomes and consumption, helping them the most during the years of the negative shocks. In the second simulation, the macroeconomic stimulus improves the performance of the economies, allowing GDP per capita to be higher than in the case of the shock alone. In summary, facing a potential global downturn as the one simulated here, those countries that have flexible exchange rates and the use of domestic monetary policies can use a mix of adjustment in exchange rates combined with targeted poverty transfers and macroeconomic stimulus to alleviate the shock. El Salvador, which does not have the exchange rate and monetary instruments, will require further support from multilateral and bilateral sources to soften the shock